2015
DOI: 10.1002/jbm.a.35433
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and bone healing properties of biomimetic porous composite scaffold:In vitroandin vivostudies

Abstract: Tissue engineering (TE) represents a valid alternative to traditional surgical therapies for the management of bone defects that do not regenerate spontaneously. Scaffolds, one of the most important component of TE strategy, should be biocompatible, bioactive, osteoconductive, and osteoinductive. The aim of this study was to evaluate the biological properties and bone regeneration ability of a porous poly(ɛ-caprolactone) (PCL) scaffold, incorporating MgCO3 -doped hydroxyapatite particles, uncoated (PCL_MgCHA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…The obtained results demonstrated that the presence of hydrophilic nanocomposite coating with higher HA content (CS/60 wt.% HA) in the SBF solution provided more nucleation sites and might accelerate the apatite mineralization and suggesting a good bioactivity [ 61 ]. It has been reported that the bioactive coatings could promote an attachment of bone to the implant and improved osseointegration between implant and host tissue [ 62 , 63 ]. These findings suggested that increased bond strength and accelerated osteoconductivity are very important aspects of CS/HA coated implant applications.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results demonstrated that the presence of hydrophilic nanocomposite coating with higher HA content (CS/60 wt.% HA) in the SBF solution provided more nucleation sites and might accelerate the apatite mineralization and suggesting a good bioactivity [ 61 ]. It has been reported that the bioactive coatings could promote an attachment of bone to the implant and improved osseointegration between implant and host tissue [ 62 , 63 ]. These findings suggested that increased bond strength and accelerated osteoconductivity are very important aspects of CS/HA coated implant applications.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, many scientists and technician have improved the osteoinductivity of bone scaffolds, by changing their physical and chemical properties or by incorporating biological constitute into the scaffolds [12]. Moreover, the porosity and pore topology structure of bone scaffolds can be modified, to enhance the osteoconductivity [13,14].…”
Section: Osteoinductivity and Osteoconductivitymentioning
confidence: 99%
“…Therefore, many scholars have improved the osteoinductivity of bone scaffolds, by changing their physical and chemical properties or by incorporating bone supplements into the scaffolds [ 17 ]. Moreover, the porosity and pore structure of bone scaffolds can be adjusted to enhance the osteoconductivity [ 18 , 19 ].…”
Section: Performance Of Materials Used In Scaffolds Designed For Bmentioning
confidence: 99%